INSTRUCTIONAL LEADERSHIP OF SCHOOL PRINCIPALS FOR IMPROVING THE QUALITY OF LEARNING IN ELEMENTARY SCHOOLS: A MULTI-SITE STUDY AT SDN KUBANG I CIANJUR AND SDN WARUNGCARINGIN BANDUNG - Ade Tutty Rokhayati Rosa; Asep Sujani; Mila Meilani; Ruri C. Hetiawati; Alpa Ruhyat (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze principals' instructional leadership strategies in improving learning quality in elementary schools through a multi-site study at SDN Kubang I Cianjur and SDN Warungcaringin Bandung. The research employed a qualitative approach with a multi-site case study design, where data were collected through in-depth interviews with 18 informants, participatory observations, and documentation studies of 47 school documents. Data were analyzed using NVivo 14 through three stages: open coding, axial coding, and selective coding. The analysis identified two equally effective patterns of instructional leadership implementation: a relationship-based pattern at SDN Kubang I and a system-based pattern at SDN Warungcaringin. Both patterns successfully improved learning achievement with literacy increasing by 12-16 percentage points and numeracy by 13-15 percentage points. Instructional supervision was the core practice with the highest coding frequency (n=156) and very positive sentiment score (0.81-0.86), implemented developmentally with high alignment (76-82%) to teacher professional development. The study concludes that instructional leadership effectiveness is determined by implementation consistency and contextual adaptation, not technological sophistication. Main challenges include high administrative burden (40-45%), technology infrastructure limitations, and teacher competency gaps. This research enriches instructional leadership literature with empirical evidence from Indonesian context and identifies the importance of curriculum change management capacity and the effectiveness of distributive instructional leadership.